2013
DOI: 10.1038/modpathol.2012.200
|View full text |Cite
|
Sign up to set email alerts
|

Value of PAX8, PAX2, claudin-4, and h-caldesmon immunostaining in distinguishing peritoneal epithelioid mesotheliomas from serous carcinomas

Abstract: Distinguishing between peritoneal epithelioid mesotheliomas and papillary serous carcinomas involving the peritoneum can be difficult on routine histological preparations, but this differential diagnosis can be facilitated by the use of immunohistochemistry. Recent investigations have indicated that PAX8, PAX2, claudin-4, and h-caldesmon are immunohistochemical markers that can assist in distinguishing between these two malignancies; however, much of the information published on the value of these markers is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 60 publications
2
44
0
Order By: Relevance
“…Claudin-3 and claudin-4 are major structural molecules of the tight junctions that link epithelial cells. Because these two claudins are frequently observed in a variety of carcinomas of different origins, but rarely detectable in mesothelial cells, several studies confirmed that claudin-3 and claudin-4 are highly specific and sensitive immunohistochemical markers for distinguishing primary or metastatic carcinomas from neoplastic or reactive mesothelium [18,19,20,21]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Claudin-3 and claudin-4 are major structural molecules of the tight junctions that link epithelial cells. Because these two claudins are frequently observed in a variety of carcinomas of different origins, but rarely detectable in mesothelial cells, several studies confirmed that claudin-3 and claudin-4 are highly specific and sensitive immunohistochemical markers for distinguishing primary or metastatic carcinomas from neoplastic or reactive mesothelium [18,19,20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…These included various epithelial markers such as carcinoembryonic antigen (CEA), Ber-Ep4, E-cadherin, MOC-31, and mucins [6,8,19,21,27,28]. However, immunocytochemical staining for these epithelial markers was unable to detect cases with MAC that did not express them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly all carcinomas were positive for PAX8 and membranous claudin-4, whereas none of the mesotheliomas exhibited reactivity with these markers. 135,136 Moreover, vascular endothelial growth factor receptor 2 (VEGFR2) was identified as a supplemental marker to identify malignant mesothelioma with promising results. Strong expression of VEGFR was demonstrated in malignant epithelioid mesothelioma but rarely in other epithelial tumors.…”
Section: Ovary the Differential Diagnosis Of Serous Carcinoma Of The mentioning
confidence: 99%